The Effect of n-Butanol Extract of Dewandaru Fruit (Eugenia uniflora L.) on the Leukocyte Count in Mice Exposed to Cigarette Smoke - Puguh Santoso; Ni Putu Febi Andani (Green Publisher Indonesia, 2026)
Dewandaru (Eugenia uniflora L.) is a medicinal plant that has been widely used in traditional medicine. Cigarettes are addictive substances that pose a significant threat to health and life sustainability. The principal toxic constituents of cigarettes are nicotine, tar, and carbon monoxide (CO). Long-term smoking can increase the total leukocyte count, particularly the number of polymorphonuclear neutrophils (PMN) in the peripheral blood circulation, due to free radical generation and inflammatory reactions. Dewandaru fruit (Eugenia uniflora L.) contains antioxidant and anti-inflammatory compounds that may inhibit leukocyte activation induced by oxidative stress associated with cigarette smoke exposure, thereby contributing to a reduction in the total leukocyte count. This study employed an experimental design with a posttest-only control group, using a sample of 30 male mice (Mus musculus) divided into three groups. Group I served as the negative control and received cigarette smoke exposure and distilled water. Groups II and III were designated as treatment groups and received 30 minutes of cigarette smoke exposure per day for 30 days, along with oral administration of n-butanol extract of dewandaru fruit at doses of 100 mg/kgBW and 200 mg/kgBW, respectively. On day 31, peripheral blood samples were collected from all subjects. The findings of this study indicate that administration of n-butanol extract of dewandaru fruit (Eugenia uniflora L.) resulted in a reduction in the total leukocyte count in male mice receiving the extract compared to the control group.